(untitled) (Economics and region, 2020)
The article is devoted to the problems of shadowing entrepreneurship in Ukraine. The shadowing entrepreneurship is one of the reasons that hinder the development of the competitiveness of our country. Based on the analysis, the main reasons for the shadowing in Ukraine are identified. The main effects of the influence of the shadow economy on the development of society are considered. The authors note a high level of the shadow economy in Ukraine and the predominantly negative nature of its influence. The main groups of negative consequences of the existence of the shadowing are identified: economic, political, social, legal. The authors also highlighted the positive effects of shadowing entrepreneurship. The articles emphasize the importance of conducting research on the shadow economy, identifying the causes of its existence, ways to reduce the level and analyze the effects on society. Understanding these effects will allow us to determine in the future the most promising ways to reduce the level of shadowing entrepreneurship.